Edukasi Pengelolaan Sampah Organik dengan Ember Tumpuk Sebagai Tindakan Nyata Kepedulian Lingkungan - Anis Khotimah; Vita Kumalasari; Lilis Rahmawati (Humanism: Journal of Community Empowerment (HJCE), 2023)
The problem of environmental pollution due to the lack of waste management is a problem that occurs in almost all regions of Indonesia. The increase in the amount of waste occurs along the measuring series while the availability of landfill land follows the counting series. This results in landfill land having a short lifespan because it is no longer able to accommodate existing waste. Household-scale waste management can be done with the concept of zero waste by applying the principles of Reduce, Reuse, Recycle (3R) is very suitable to be applied in developing countries due to technological limitations, so it must empower the community as actors who produce waste. The concept of waste recycling and composting is able to reduce the waste that is transported to the TPS/TPA in Kebonmanis Village, Cilacap by 75%, from 23,638 m3/day to 5,821 m3/day (Ika W, 2010). Zero waste is basically not management until no more waste is produced because there is no human activity that does not produce waste. By paying attention to these conditions, the community service team concluded that it is necessary to overcome the waste problem starting from the household level, by organizing a household waste management counseling activity. The method used in this community service is in the form of counseling. The method used in this community service is in the form of counseling in Purworejo, Wonolelo, Pleret, Bantul, Yogyakarta so that community members know how to manage organic waste as a tangible proof of concern for the environment. The community of Purworejo, Wonolelo, Pleret, Bantul, Yogyakarta showed increased knowledge after counseling on waste management education. There is a difference in knowledge before and after the provision of health education about organic waste management using a piling bucket.